Variability and clinical value of troponin T levels in diabetic kidney disease patients treated with dialysis - Yu Rui; Cheng Cui-cui; Zhang Shan; Yang Xiao-xia; Sun Xin-yu; Gao Qing-zhen (Linchuang shenzangbing zazhi)
ObjectiveTo determine the variation of troponin T （TnT） in diabetic kidney disease （DKD） patients treated with dialysis， and to evaluate its clinical value.MethodsA total of 8，553 DKD patients treated with dialysis and examination of TnT values were screened in Jinan Central Hospital from January 1， 2014 to August 31， 2020. Screened by inclusion and exclusion criteria， 5，692 patients were excluded. After excluding 2，485 cases with unavailable TnT data， finally， 376 eligible patients were included into our study. They were divided into DKD dialysis group and non-DKD （NDKD） dialysis group based on the primary disease. Baseline TnT was compared between the two groups， and the optimal threshold to diagnose acute myocardial infarction was determined by plotting the receiver operating characteristic （ROC） curves. Influencing factors for baseline TnT in DKD patients treated with dialysis and their correlation with poor prognosis were analyzed.ResultsBaseline TnT in the DKD dialysis group （267.27 ng/L） was significantly higher than that in the NDKD dialysis group （76.09 ng/L）， which was 3.51 times higher. The optimal threshold of baseline TnT for the diagnosis of acute myocardial infarction was 166.85 ng/L in NDKD dialysis group， and 367.45 ng/L in DKD group. Higher baseline TnT were detected in men than women in the DKD dialysis group. Baseline TnT was positively associated with age， degree of DKD， and degree of lower extremity vasculopathy， but negatively correlated with hemoglobin and albumin. With the increase in baseline TnT， the rate of myocardial infarction， psychogenic mortality， diabetic foot ulcer， and all-cause mortality increased in DKD dialysis group.ConclusionBaseline TnT is significantly higher in the DKD dialysis group than that of the NDKD dialysis group， and a higher threshold is required for the diagnosis of acute myocardial infarction. Elevated baseline TnT level is influenced by factors such as diabetic vascular complications， which can be used as a prognostic indicator for adverse events.